Advances in chronic obstructive pulmonary disease: management of exacerbations. (2nd July 2022) - Jeyachandran, Varun; Hurst, John R
Abstract : Exacerbations of chronic obstructive pulmonary disease are important events to people living with this condition and a common cause of emergency hospital admission. In the absence of a confirmatory biomarker, an exacerbation remains a clinical diagnosis of exclusion and clinicians must be alert to alternative diagnoses. Most exacerbations are caused by airway infection, particularly with respiratory viruses. The mainstay of exacerbation treatment is an increase in the dose and/or frequency of short-acting beta-agonists, with short-course oral corticosteroids and/or antibiotics. Although there have been no new interventions to treat exacerbations in many years, there is still much variation in care and opportunity to improve outcomes. There has been a new focus on both the management of comorbidities and the optimisation of future care to reduce the risk of further events. This review summarises advances in managing exacerbations of chronic obstructive pulmonary disease, focusing on hospitalised patients.